2018
DOI: 10.1111/ajt.14545
|View full text |Cite
|
Sign up to set email alerts
|

Use of thrombolytic therapy in DCD liver transplantation does not seem to improve outcome

Abstract: The authors compared 100 consecutive donation after circulatory death (DCD) liver transplantations (LT) using a protocol that includes thrombolytic therapy (late DCD group) to a historical DCD group (early DCD group) and a cohort of donation after brain death (DBD) LT. The primary objective of the study was to "present the experience with 100 consecutive DCD LT using a protocol that includes tissue plasminogen activator (tPA) administration."While the team at Ochsner Clinic Foundation, New Orleans, deserves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…4,11,14,25,26,32,33 Assessment of graft survival and biliary complications in DCD liver transplantation has shown that donor age, donor WIT greater than 30 minutes and CIT greater than 10 hours are highly predictive of poor graft outcomes compared to DBD liver transplantation. 4,14,25,30 In our present series, compared to patients in the early era, those in the late era had a significantly shorter time to cannulation and flush, lower WIT and a trend toward decreased CIT. These improvements likely explain the significant reductions in biliary complication rates achieved in the late era.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…4,11,14,25,26,32,33 Assessment of graft survival and biliary complications in DCD liver transplantation has shown that donor age, donor WIT greater than 30 minutes and CIT greater than 10 hours are highly predictive of poor graft outcomes compared to DBD liver transplantation. 4,14,25,30 In our present series, compared to patients in the early era, those in the late era had a significantly shorter time to cannulation and flush, lower WIT and a trend toward decreased CIT. These improvements likely explain the significant reductions in biliary complication rates achieved in the late era.…”
Section: Discussionmentioning
confidence: 45%
“…Although different groups have shown promising results with this practice, 28,29 recent evidence from a group in the Netherlands shows no reduction in nonanastomotic biliary strictures from the use of urokinase before liver transplantation. 30 We believe that the low rates of IC attributed to thrombolytic therapy are actually due to the multifactorial effect of accumulating experience with DCD liver transplantation (i.e., proper donor/recipient selection and shorter ischemic times). In our DCD liver transplantation protocol, we do not use thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has shown that routine use of tPA in the setting of DCD transplant may be one cost‐effective strategy for prevention of NAS in this particularly susceptible population . Recently, however, other studies have called into question the role of microthrombi in biliary stricture development after DCD transplantation as well as the utility of tPA in reducing biliary stricture incidence DCD liver transplant recipients, pointing toward the need for a multi‐institution, randomized trial to more clearly assess the value of routine tPA use in DCD transplantation for prevention of biliary strictures …”
Section: Discussionmentioning
confidence: 99%
“…Urokinase (UK), a proteolytic enzyme that catalyzes the conversion of plasminogen to plasmin, has widespread applications in thrombolytic therapy . UK is often derived from human urine and animal cell culture, with the former serving as the major source .…”
Section: Introductionmentioning
confidence: 99%